Impact of water stress and CO2 enrichment on growth and fiber development of kenaf (Hibiscus cannabinus L.) - Khalatbari, Amir Mahdi (2015)
In this study, the effect of some environmental factors (different water treatments and CO2 concentration) on morphological, physiological and histochemical characteristics of some kenaf varieties namely Fuhong (FH991, FH992 and FH952), V36, Kohn-Kaen60 (KK60) and TK were considered. Kenaf (Hibiscus cannabinus L.), a fast growing C3 plant native of tropical Africa, is being investigated as a new source of bioenergy as well as an industrial crop and has high potential to be used in Malaysia. Kenaf is considered as a great source of cellulose fiber for a wide range of paper products. Information on lignocellulose properties (lignin and cellulose) of these kenaf varieties as affected by environmental factors such as water stress, time of water stress imposition and CO2 enrichment are still scarce and such data would be useful to provide information on fiber products containing high levels of lignocellulose attributes. A Randomized Complete Block Design (RCBD) experiment was conducted to determine performance and growth rate of varieties namely Fuhong (FH991, FH992 and FH952), V36, Kohn-Kaen60 (KK60) and TK during the seedling establishment. Seedling establishment is one of plant’s growth phases in which some of the factors are precisely influential in final stage of growth and development for kenaf which is known as fiber product. The results showed that different varieties had significant effects on growth parameters such as shoot height and stem diameter which are important for producing higher fibre content and yield. Varieties FH991 and V36 obtained higher values of plant height (74.2 cm and 72 cm respectively) and stem diameter (5.53 mm and 5.50 mm) whereas variety KK60 recorded the lowest value for root parameters such as root average diameter value which was 0.62 mm. These three varieties were selected for further studies for their fiber yield and quality evaluation. A split plot experiment was arranged to determine effect of three different water treatments (100% ER; well watered, 50% ER; high water stress and 25% ER; severe water stress) on morphological,physiological, fiber yield and lignocellulose quality of varieties FH991, V36 and KK60. The highest plant height belonged to variety FH991at 100% of ER and followed by variety V36 (242.67 cm and 230.66 cm respectively) whereas variety KK60 with water treatment of 25% of ER obtained the lowest average height of 190.67 cm at the end of experimental period. The highest net photosynthesis rate belonged to variety FH991 at 100% of ER with the value of 23.57 μmol m-² s-1 at the end of experimental period. The lowest net photosynthesis rate 10.87 of μmol m-² s-1 was recorded by variety V36 at 25% of ER. The highest fiber length fore bast was recorded by varieties FH991 and V36 (2.59 mm and 2.57 mm respectively) at 100% ER. The highest fiber length of core belonged to varieties V36 and FH991 with 100% ER recording the value of 0.95 mm and 0.93 mm respectively. The lowest fiber length for bast belonged to variety V36 at 25% ER with the value of 1.32 mm. The lowest fiber length for core was recorded by variety KK60 with the value of 0.48 mm. The optimum value of bast fiber yield was obtained by variety V36 with 100% ER water treatment (13.3 g plant-1) followed by variety FH991 (12.96 g plant-1) and KK60 (11.77g plant-1) respectively. The lowest value for bast fiber yield was recorded by variety V36 at 25% ER (4.98 g plant-1). The highest core fiber yield of 21.72 g plant-1 belonged to variety FH991with 100% ER water treatment which was followed by variety V36 with value of 21.32 g plant-1Variety V36 at 25% ER attained the lowest value of 8.44 g plant-1. The evidence from this study elucidated that the fiber quality of for all three varieties decreased by increasing the severity of water stress from 100% ER to 25% ER. For the third experiment a split plot experiment was arranged to determine effect of three different times of water stress imposition at different growth stages namely daily watering (100% ER; well watered), water stress imposition 1 month after seedling establishment completion (1MAS) and finally water stress imposition at flowering stage (AFS) on morphological and histochemical attributes of varieties FH991, V36 and KK60. The highest value of net photosynthesis rate belonged to variety FH991 (23.33 μmol m-2s-1) and it was followed by varieties KK60 with value of 23.27 μmol m-2s-1and V36 at 21.63 μmol m-2s-1. The lowest net photosynthesis rate of 11.37 μmol m-2s-1belonged to variety KK60 subjected to water treatment of 1MAS. Considering the impact of different water treatments on fiber dimensions of these varieties, the highest bast and core fiber length of 2.59 mm and 0.91 mm was recorded when all varieties were under control water treatment (no stress). The lowest bast and core fiber length belonged to water treatment of 1MAS with value of 1.62 mm and 0.64 mm respectively. The highest bast holocellulose, α-cellulose and lignin belonged to varieties under control treatment (85.22%, 56.42% and 13.75% respectively). Core lignocellulose attributes attained highest percentages under control water treatment in which holocellulose recorded 83.17%, α-cellulose 46.85% and lignin 20.08%. The lowest bast and core lignocelluloses belonged to varieties under water stress treatment of 1MAS. Bast holocellulose of 80.67%, α-cellulose of 56.42 and lignin of 13.75% were recorded when plants were under water stress of 1MAS. Plants under water stress treatment of 1MAS had lowest core holocellulose of 78.63%, α-cellulose of 41.97% and lignin of 15.24. As an interesting result water stress imposition at flowering stage increased bast fiber length and core lumen diameter for selected varieties that could describe possible positive effect of water stress imposition in this stage of growth on kenaf fiber dimension. For the last experiment varieties FH991, V36 and KK60 were exposed to 400 and 800 μmol mol-1 CO2 in a split plot experiment. Results of the analysis of variance showed that different CO2 concentrations (400 μmol mol-1 and 800 μmol mol-1) had significant impact on morphological, physiological and histochemical properties of all three varieties for all traits measured; indicating enriched CO2 level (800 μmol mol-1) had a huge impact on measured traits. The highest bast fiber length was recorded by 800 μmol mol-1 CO2 level with value of 3.10 mm whereas CO2 level of 400 μmol mol-1 recorded bast fiber length of 2.68 mm. For core fiber attributes, the highest core fiber length belonged to elevated CO2 level (800 μmol mol-1) with value of 0.98 mm whereas ambient CO2 level (400 μmol mol-1) recorded core fiber length of 0.92 mm. The highest bast holocellulose, α-cellulose and lignin belonged to varieties under enriched CO2 level of 800 μmol mol-1 (87.34%, 57.85% and 14.32% respectively). Core lignocellulose attributes attained highest percentages under elevated CO2 level (800 μmol mol-1) in which holocellulose recorded 84.24%, α-cellulose 47.52% and lignin 21.60%. The most obvious finding to emerge from this study is that CO2 enriched kenaf plants exhibited the ability to synthesize higher fiber yield and lignocellulose properties which were not detected from kenaf grown under ambient CO2 concentration. These results indicate that the fiber yield and histochemical attributes of these kenaf varieties can be enhanced by controlled environment production and CO2 enrichment in top soil.